Les elephants Loxodonta africana dans la reserve de Biosphere de la Pendjari nord-est Republique du Benin: abondance, densite et repartition spatiale - Tehou, Aristide (Pachyderm, 2002)
Reviews the status of elephants (with reference to surveys in 1987, 1990, 2000-2002) in Pendjari Biosphere Reserve in northwest Benin and compares recent figures with the density and abundance in other protected areas in the immediate area (Arly, Pama, W Park). Both aerial and ground surveys have been undertaken and the populations observed and/or estimated vary widely thus the author suggest that the ground survey counts in the central region (Pendjari NP) over the past three years be considered. However, due to migration patterns, here too the counts very widely with 433, 428 and 2607 animals being observed in 2000, 2001 and 2002 respectively. The author suggests counts and estimates should become more accurate as management capacity develops with the creation of a national centre for faunal reserves.